Pelatihan Self-Branding dan Bahasa Inggris Untuk Menjadi Caregiver di Tataran Global - Nurhana, Riza; Alfianto, Ahmad Guntur; Sulaksono, Ari Dwi (Penerbit Goodwood, 2025)
Purpose: This program aims to increase the self-confidence of students majoring in nursing assistants at SMK NU Miftakhul Huda in communicating in English and providing good and quality care services as their target situation as caregivers in a global setting. Methodology/approach: This program was implemented at SMK NU Miftakhul Huda in the Kepanjen District of Malang Regency, East Java. The partners were 14 class XII students. The method was divided into three sessions: brainstorming, discussion, lectures, case studies, and practice approaches. The tools used for measurement were questionnaires and English practice observation sheets. Results/findings: There was a change in English language skills and knowledge about self-branding (0.000), and practice skills of basic English in health (75.72 ± 12.65), which had a very good meaning. Conclusion: he training program successfully improved students’ English communication skills and self-branding competence, which are essential for preparing them as caregivers in a global setting. The results demonstrate significant progress in knowledge, confidence, and practical abilities, indicating that continuous training and support will strengthen their readiness to compete in the international workforce in the future. Limitation: Partner's motivation and interest in speaking English, the need for familiarization, and repetition of English language competence. Contribution: This program has an impact on the school as a vocational school by improving students’ English competence as a working language in a global setting and self-branding for preparation for work as a form of self-promotion and self-confidence.